Volatility Spillover Effect of Macroeconomic Indicators on Inflation: A BEKK-GARCH Approach (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
This study aims to examine the transmission of macroeconomic volatility—specifically, exchange rates and bond yield spreads—to inflation volatility, using monthly data from January 2012 to December 2024. The research begins with univariate modeling, employing GARCH and EGARCH to elucidate the volatility characteristics of each variable. The findings indicate that inflation and exchange rates exhibit asymmetric volatility, while the bond yield spread demonstrates a symmetric pattern. Furthermore, this study uses a multivariate BEKK-GARCH methodology to examine the influence of volatility from key macroeconomic indicators—specifically, the exchange rate and bond yield spread—on inflation in Indonesia. The results of the BEKK-AGARCH(1,1) model demonstrate significant volatility spillovers, notably a bidirectional link between inflation and the currency rate. Furthermore, this analysis confirms an asymmetric spillover effect from bond yield spreads to inflation, indicating that inflation volatility is more profoundly affected by negative shocks in the bond market than by positive shocks. The research highlights the necessity of monitoring macroeconomic volatility, as it profoundly affects the efficacy of monetary policy and inflation stability. This research offers policymakers crucial information to build more flexible methods for addressing inflation threats in an ever-evolving macroeconomic environment.